Effect of Pulmonary Inflammation by Surface Functionalization of Zinc Oxide Nanoparticles - Ayoung Jung; Sung-Hyun Kim; Jun-Young Yang; Jayoung Jeong; Jong Kwon Lee; Jae-Ho Oh; Jin Hee Lee (Toxics, 2021)
Zinc oxide nanoparticles (ZnO NPs) are used in various industries such as food additives, cosmetics, and biomedical applications. In this study, we evaluated lung damage over time by three types of ZnO NPs (L-serine, citrate, and pristine) following the regulation of functional groups after a single intratracheal instillation to rats. The three types of ZnO NPs showed an acute inflammatory reaction with increased LDH and inflammatory cell infiltration in the alveoli 24 h after administration. Especially in treatment with L-serine, citrate ZnO NPs showed higher acute granulocytic inflammation and total protein induction than the pristine ZnO NPs at 24 h. The acute inflammatory reaction of the lungs recovered on day 30 with bronchoalveolar fibrosis. The concentrations of IL-4, 6, TNF-α, and eotaxin in the bronchoalveolar lavage fluid (BALF) decreased over time, and the levels of these inflammation indicators are consistent with the following inflammatory cell data and acute lung inflammation by ZnO NP. This study suggests that single inhalation exposure to functionalized ZnO NPs may cause acute lung injury with granulocytic inflammation. Although it can recover 30 days after exposure, acute pulmonary inflammation in surface functionalization means that additional studies of exposure limits are needed to protect the workers that produce it.